Complex assessment of injuriousness and harmfulness of terat-forming aphids-pests of ornamental woody plants in green areas in Belarus: current situation and its change since 2007 - Petrov, Dmitry L. (Journal of the Belarusian State University. Ecology, 2019)
Based on current expert assessments of 7 parameters, the indexes of physiologically conditioned injuriousness (physiological injuriousness), environmentally conditioned and general harmfulness of 55 species of terat-forming aphids – pests of ornamental woody plants in green areas in Belarus are calculated. The maximum values of indexes of physiological injuriousness are for the monoecious aphid species, such as Cinara pinea Mordv. and Cinara pilicornis Hart., inhabiting woody plants during the entire growing season. Ecologically conditioned harmfulness is maximal (27 points) for Brachycaudus spiraeae Börn., Colopha compressa Koch, Eriosoma ulmi L., Myzaphis rosarum Kalt., Pemphigus bursarius L. и Pemphigus spyrothecae Pass., while general harmfulness – for black legume aphid (Aphis craccivora Koch) – 229,5 points. For more than a decade, the index values of the physiological injuriousness of non-migratory species of aphids increased due to increasing of the duration of their development on host plants following the increase of the length of the growing season. The index values of environmentally conditioned harmfulness increased for Myzus ligustri Mosley, Myzus pruniavium Börn., and Phyllaphis fagi L. as a result of increased presence of their host plants in green areas. The general harmfulness of Dysaphis ranunculi Kalt., Hyadaphis tataricae Aiz. and B. spiraeae decreased due to a large-scale removal of their host plants from green areas.
Keywords: ornamental plantings; Aphidoidea; pests; introducents